2010
DOI: 10.1021/bi100490u
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Functional Metal Binding Profile of a CdII/PbII Sensor CmtRSc from Streptomyces coelicolor

Abstract: Metal homeostasis and resistance in bacteria is maintained by a panel of metal sensing transcriptional regulators that collectively control transition metal availability and mediate resistance to heavy metal xenobiotics, including AsIII, CdII, PbII and HgII. The ArsR family constitutes a superfamily of metal sensors that appear to conform to the same winged helical, homodimeric fold, that collectively “sense” a wide array of beneficial metal ions and heavy metal pollutants. The genomes of many actinomycetes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
(132 reference statements)
0
13
0
Order By: Relevance
“…Microorganism present in soil and water has the ability to produce volatile compounds that are less toxic from organic and inorganic leading compounds ( Kohli et al, 2019 , Abd_Allah et al, 2019 ) and it can be attributed to the present study. For the proper growth in presence of metals these species may have created a protective system as an additional component in relation to cytochrome c in the ultimate part of the respiratory chain, which is not inactivated by the metal ( Wang et al, 2010 , Lima e Silvaet al, 2012 ). Lead resistance in the microorganisms is also acquired by limiting their movement across the cell envelope ( Rahman et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microorganism present in soil and water has the ability to produce volatile compounds that are less toxic from organic and inorganic leading compounds ( Kohli et al, 2019 , Abd_Allah et al, 2019 ) and it can be attributed to the present study. For the proper growth in presence of metals these species may have created a protective system as an additional component in relation to cytochrome c in the ultimate part of the respiratory chain, which is not inactivated by the metal ( Wang et al, 2010 , Lima e Silvaet al, 2012 ). Lead resistance in the microorganisms is also acquired by limiting their movement across the cell envelope ( Rahman et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis is a self-regulating core feature of biological organisms that allows them to, whenever possible, maintain their internal stability and keep a constant physiological state. There are a number of homeostatic process that must be preserved in order to guarantee the survival of the organism including iron homeostasis, metal homeostasis, pH homeostasis and membrane and lipid homeostasis [ 4 , 5 , 6 , 7 , 8 ]. Since the beginning of life on this planet, microbes have been exposed to metals—some necessary, but many that are toxic to the cells [ 9 ].…”
Section: Physiological Acclimation and Evolutionary Adaptationmentioning
confidence: 99%
“…Virtually all bacteria have acquired genes that control their physiology, allowing them to resist toxic metal ions (Ag + , Cd 2+ , Hg 2+ , Ni 2+ etc.). To deal with these toxic metals, many bacteria express metal-sensing transcriptional regulators that can sense both beneficial and toxic metals allowing them to adapt to their environments rather quickly and as a result, energy dependent efflux is the most commonly deployed metal resistance mechanism among microorganisms [ 5 , 9 ]. Our studies showed this for both ionic and nanosilver (Ag + ) based resistance in E. coli [ 2 , 10 ].…”
Section: Physiological Acclimation and Evolutionary Adaptationmentioning
confidence: 99%
“…ArsR/SmtB family 1147 Under conditions of metal excess, members of the ArsR/SmtB family 1148 regulate intracellular metal-ion concentrations by functioning as 1149 metallo-regulatory sensors (reviewed in [32]). In contrast to other clas-1150ses of prokaryotic metal sensors, the ArsR/SmtB members seem to func-1151 tion exclusively as transcriptional repressors[279,280].…”
mentioning
confidence: 99%